Writing the aerial dancing body a preliminary choreological investigation of the aesthetics and kinetics of the aerial dancing body - Acker, Shaun Albert (Rhodes University, Faculty of Humanities, Department of Drama, 2010)
This mini-thesis investigates some of the nineteenth century socio-cultural ideals that have structured a connection between virtuosic aerial skill and bodily aesthetics. It views the emergence of a style of aerial kineticism that is structured from the gender ideologies of the period. It investigates the continual recurrence of this nineteenth century style amongst contemporary aerial dance works and outlines the possible frictions between this Victorian style of kineticism and contemporary aerial explorations. From this observation, a possible catalyst may be observed with which to relocate and inspire a study of aerial kinetics sans the nineteenth century aesthetic component. This kinesiological catalyst may be viewed in conjunction with the theories of ground-based kinetic theorist, Rudolph Laban's choreutic study of the body in space. Thus, it may be possible to suggest and introduce a possible practical dance scholarship for aerial dance. This mini-thesis includes an introductory choreological investigation that draws on and integrates the disciplines of kinesiology; choreutic theory; existing aerial kinetic technique; musicology; and the physical sciences.
Keywords: Dance -- 19th century; Dance -- 20th century Dance -- 21st century; Aerialists; Movement, Aesthetics of; Feminine beauty (Aesthetics); Movement notation